2019
DOI: 10.1186/s13104-019-4801-3
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species validation of human specific STR system, SureID® 21G and SureID® 23comp (Health Gene Technologies) in Chimpanzee (Pan Troglodytes)

Abstract: ObjectivesThe human specific commercially available STRs system are often not tested in non human primates for their cross applicability. The aim of this study is to test Cross-species validation of two commercially available human specific STR kits i.e. SureID® 21G and SureID® 23comp (Health Gene Technologies) for their positive application in Chimpanzee (Pan troglodytes).ResultIn SureID® 21G, 19 loci amplified and while 20 loci amplified in SureID® 23comp. All the amplified loci in both STR kits were found p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…As the lyophilized SureID®S6 system was built based on a former SureID system with the liquid amplification reagent, the cross-species validation results of the SureID system could help us to get acquainted with the species specificity of the SureID®S6 system. The cross-species validation ( Singh et al, 2019 ) of the SureID system in Chimpanzee showed that all the revealed loci were polymorphic and the Amelogenin gene yielded identifiable banding patterns between male and female Chimpanzees. In the present study, we only paid attention to the possible cross-reactivity of the SureID®S6 system against human-associated non-primate animals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the lyophilized SureID®S6 system was built based on a former SureID system with the liquid amplification reagent, the cross-species validation results of the SureID system could help us to get acquainted with the species specificity of the SureID®S6 system. The cross-species validation ( Singh et al, 2019 ) of the SureID system in Chimpanzee showed that all the revealed loci were polymorphic and the Amelogenin gene yielded identifiable banding patterns between male and female Chimpanzees. In the present study, we only paid attention to the possible cross-reactivity of the SureID®S6 system against human-associated non-primate animals.…”
Section: Resultsmentioning
confidence: 99%
“…As the lyophilized SureID ® S6 system was built based on a former SureID system with the liquid amplification reagent, the cross-species validation results of the SureID system could help us to get acquainted with the species specificity of the SureID ® S6 system. The cross-species validation (Singh et al, 2019) of the SureID system in Chimpanzee showed that all the revealed loci were polymorphic and the Amelogenin FIGURE 3 | Peak heights for male control DNA 9948 when the following template amounts were amplified: 1 ng, and 500, 250, 125, 62.5, and 31.25 pg. The peak height ranges were color-coded as follows: <500 RFUs (blue), 500-2,300 RFUs (yellow), 2,301-12,000 RFUs (green), 12,001-20,000 RFUs (pink), and >20,000 RFUs (orange).…”
Section: Species Specificitymentioning
confidence: 99%
“…The genetic diversity analysis and genealogical relationship analysis revealed higher heterozygosity with several alleles and Delta Ln(L) with a value of 9999 indicating that the examined chimpanzees were genetically unrelated. In the previous attempts of amplification of human specific STR markers in chimpanzees, Thakur et al [ 9 ] and Singh et al [ 10 ] revealed that the majority of the loci showed positive amplifications with SureID® 23comp identification system having highest mean heterozygosity (Table 1 ). Therefore, the study establishes the fact that the human specific identification systems i.e.…”
Section: Main Textmentioning
confidence: 99%
“…Further, to assess the extent of amplification of human STR markers in non-human primates, few recent studies i.e. Thakur et al [ 9 ] and Singh et al [ 10 ] performed cross-species validation of several commercial forensic STR kits in chimpanzees. These studies also assessed the power of individual identification of forensically important markers in chimpanzees.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the extent of ampli cation of Human STR markers in non-human primates, few earlier studies i.e. Thakur et al [4] and Singh et al [5] performed cross-species validation of several commercial forensic STR kits in Chimpanzees. These studies also assessed the power of individual identi cation of forensically important markers in the case of Chimpanzees.…”
Section: Introductionmentioning
confidence: 99%